The RNA Methyltransferase NSUN2 and Its Potential Roles in Cancer - Chellamuthu, Anitha; Gray, Steven G. (Cells (Basel, Switzerland), 2020)
5-methylcytosine is often associated as an epigenetic modifier in DNA. However, it is also found increasingly in a plethora of RNA species, predominantly transfer RNAs, but increasingly found in cytoplasmic and mitochondrial ribosomal RNAs, enhancer RNAs, and a number of long noncoding RNAs. Moreover, this modification can also be found in messenger RNAs and has led to an increasing appreciation that RNA methylation can functionally regulate gene expression and cellular activities. In mammalian cells, the addition of m5C to RNA cytosines is carried out by enzymes of the NOL1/NOP2/SUN domain (NSUN) family as well as the DNA methyltransferase homologue DNMT2. In this regard, NSUN2 is a critical RNA methyltransferase for adding m5C to mRNA. In this review, using non-small cell lung cancer and other cancers as primary examples, we discuss the recent developments in the known functions of this RNA methyltransferase and its potential critical role in cancer.